Pneumothorax and pneumomediastinum among COVID-19 patients with mechanical ventilation: a case series - Kartika Luthfiana; Achmad Faisal; Bramastha Aires Rosadi (Intelektual Pustaka Media Utama, 2023)
The incidence of pneumothorax is 10% of all COVID-19 patients and increases in patients who develop acute respiratory distress syndrome (ARDS) with mechanical ventilation, responsible for 24% of the population. As many as 60.7% of patients who have complications of pneumothorax or pneumomediastinum lead to mortality. This study was established to determine the potential of early tracheostomy in preventing the occurrence of pneumothorax and pneumomediastinum in COVID-19 and reducing mortality. This research was conducted as a descriptive study by case series of three COVID-19 patients in Jakarta, Indonesia in the span of 2021-2022. Tracheostomy performed within 10 days, did not develop a pneumothorax. Although, the patient did not have any comorbidities, age below 70 years, and coagulopathy problem, there was still a risk of recurrent pneumothorax post COVID-19 after tracheostomy. However, a tracheostomy is a procedure that poses an aerosol risk, so there is concern about the transmission of COVID-19 to medical personnel who perform it. Early tracheostomy has the potential to accelerate the resolution of COVID-19 disease in patients and has a positive impact on lung vitality. It is aimed to prevent hypoxic conditions and optimize the lung recruitment process. In addition, they did not experience complications from COVID-19 in the form of an air leak syndrome such as a pneumothorax or pneumomediastinum.